(untitled) (Agroindustrial Science, 2025)
Spent coffee grounds (scg), Coffea spp, is an unvalued waste material. Contains bioactive compounds and minerals, which can be used as organic amendments to improve agricultural soils quality. The objective of the research was to evaluate the change in physical and physicochemical properties of two agricultural soils by adding scg directly, as well as adding compost obtained from a 75/25 v/v mixture of scg/ bovine manure as biofertilizer to increase the growth of chili seedlings (Capsicum annuum). The direct addition of 10% scg to soil increased physical properties such as saturation point, field capacity and permanent wilting point, decreasing the apparent density. The chemical properties and germination index (GI) increased with both addition, 10% and 20%. The pH is adequate only with the addition of 10%. Chili seedling development was not good with direct addition of scg. The physicochemical properties and GI of compost obtained from 75/25 v/v mixtures meet the Mexican regulatory requirements for its use. The addition of 6% compost significantly increases (p ≥ 0.05) the yield of habanero peppers, while the increase in poblano and mirasol peppers is achieved with 25%.